Characterization of the depocenters and the basement structure, below the central Chile Andean Forearc: A 3D geophysical modelling in Santiago Basin area. (1st March 2018) - González, Felipe Andrés; Maksymowicz, Andrei; Díaz, Daniel; Villegas, Luis; Leiva, Maximiliano; Blanco, Bárbara; Vera, Emilio; Contreras, Sergio; Cabrera, Daniel; Bonvalot, Sylvain
Abstract: Since the last century, several geological and geophysical studies have been developed in the Santiago Basin to understand its morphology and tectonic evolution. However, some uncertainties regarding sedimentary fill properties and possible density anomalies below the sediments/basement boundary remain. Considering that this is an area densely populated with more than 6 million inhabitants in a highly active seismotectonic environment, the physical properties of the Santiago Basin are important to study the geological and structural evolution of the Andean forearc and to characterize its seismic response and related seismic hazard. Two and three‐dimensional gravimetric models were developed, based on a database of 797 compiled and 883 newly acquired gravity stations. To produce a well‐constrained basement elevation model, a review of 499 wells and 30 transient electromagnetic soundings were used, which contribute with basement depth or minimum sedimentary thickness information. For the 2‐D modelling, a total of 49 gravimetric profiles were processed considering a homogeneous density contrast and independent regional trends. A strong positive gravity anomaly was observed in the centre of the basin, which complicated the modelling process but was carefully addressed with the available constrains. The resulting basement elevation models show complex basement geometry with, at least, eight recognizable depocenters with maximum sedimentary infill of ~ 500 m. The 3‐D density models show alignments in the basement that correlates well with important intrusive units of the Cenozoic and Mesozoic. Along with interpreted fault zones westwards and eastwards of the basin, the observations suggest a structural control of Santiago basin geometry, where recent deformation associated with the Andean contractional deformation front and old structures developed during the Cenozoic extension are superimposed to the variability of river erosion/deposition processes.